Analisis Kondisi Keuangan Guru Honorer di Jawa Barat dan Implikasinya pada Penggunaan Pinjaman Online - Nabhani, Irfan; Nabhani, Mikail Omar; Fitri, Liani Asmarani (Institut Teknologi Garut, 2024)
This article aims to provide a descriptive analysis regarding the conditions of honorary teachers in West Java in financial management. This is important because honorary teachers are one of the spearheads of education at the primary and secondary levels whose welfare needs attention. This research also carries out discussions and proposes a research framework concept on the factors that influence this behavior, including their decisions when taking online loans. The survey was conducted online on 68 honorary teachers who are members of the association for further descriptive analysis. The survey results show that the majority of honorary teachers have incomes that are below living standards so their position will be vulnerable to penetration by online loans, especially illegal ones. This research proposes a further research concept on the financial behavior of regional honorary teachers by including the variables of financial literacy, inclusiveness, efficiency and innovation, risk and customer protection, security and confidentiality of personal data, as well as the legality of the loan.